Idealized Bodies and the Visual Turn after the First World War: American Children's Public Health Campaigns. Issue 1 (April 2022) - Monteyne, Kimberley
Abstract : As children's public health education in the United States became significantly invested in visual instruction and pleasurable learning experiences following World War I, these methods sought to redefine healthy bodies through a twofold approach: appeals to the burgeoning film industry and idealized celebrity bodies, and a wide-reaching program of statistical measurement initiatives. In this process the child's body was reimagined through the trope of the movie star – an immaterial and depthless projection immune from the physical effects of war – and also abstracted via mass statistical measurement programs that paralleled contemporary eugenics practices. Both methods aimed at a de-materialization of the body to ward off the painful reality of physically weak, malnourished children and the badly damaged bodies of returning veterans. Thus, post-WWI children's health education became an ambivalent corporeal topography in which the body functioned as a site of play and imaginative edification caught between the deeply misguided scientific idealism of eugenics and new forms of presenting physical perfection through modern cinema and beauty culture.